POLA PERTUMBUHAN DAN FAKTOR KONDISI IKAN SELUANG (Rasbora argyrotaenia) DI DANAU TELUK KENALI KOTA JAMBI - Maulida, Syafira; Gelis, Ester Restiana Endang; Lisna, Lisna; Nelwida, Nelwida; Arfiana, Bs Monica; Farizal, Farizal (Mantis Journal of Fisheries, 2025)
Teluk Kenali Lake is located in Teluk Kenali Village, Telanaipura District, Jambi City, with an area of approximately 30 ha, and has a water characteristic in the form of a basin. The main catch of fishermen in this lake is the seluang fish, which is popular with the community because of its taste and high economic value. This study used a purposive sampling method through direct observation of fishermen's catches. Samples were obtained from the catch of two fishermen using gillnet fishing gear with a mesh size of 1 inch during a 1-month study. The results showed that male seluang fish had an average length of 8.6 cm and an average weight of 4.9 g, with a b value in the length-weight relationship analysis of 2.88, a determination coefficient of 0.91, and a condition factor (K) of 1.75, indicating a less flat body. Female seluang fish had an average length of 9.04 cm and an average weight of 6.26 g, with a b value of 0.94, a determination coefficient of 0.18, and a condition factor of 1.99, indicating a less flat body. It was concluded that the growth pattern of male and female seluang fish was negatively allometric (b < 3), which means that length growth was more dominant than weight growth.